Tile rear extension module for the phase-I upgrade of the ATLAS L1Calo preprocessor system - Andrei, George Victor; Hanke, Paul; Harion, Tobias; Schmitt, Klaus; Schultz-Coulon, Hans-Christian; Stamen, Rainer; Stock, Peter (Journal of Instrumentation, 2017)
After the Phase-I ATLAS upgrade the Tile calorimeter will have to provide its data via fast optical links to the new Feature Extractor (FEX) modules of the L1Calo trigger system. In order to provide the FEXes with digitised Tile data, new Tile Rear Extension (TREX) modules need to be developed and installed in the existing L1Calo PreProcessor system. The TREX modules are highly complex PCBs, with state-of-the-art FPGAs and high-speed optical transmitters working at rates up to 14 Gbps. The prototype design of TREX and first corresponding test results will be presented.